Aerophilic Electrode with Cone Shape for Continuous Generation and Efficient Collection of H2 Bubbles. (8th August 2016) - Yu, Cunming; Cao, Moyuan; Dong, Zhichao; Li, Kan; Yu, Cunlong; Wang, Jingming; Jiang, Lei
Abstract : Hydrogen as a sustainable and clean energy source has attracted great attention with the increasing global energy crisis. However, sufficient production of hydrogen is seriously impeded by the adhesion of hydrogen bubble to electrodes. Efficient removal of hydrogen bubbles attached to the electrode can improve the efficiency of the hydrogen evolution reaction. Following this concept, numerous approaches to shorten the adhesion time of hydrogen bubbles on electrodes have been presented, such as ultrasonic treatment and electrode surface micro/nano‐modification. Almost all of the existing solutions are based on the instant and direct release of generated hydrogen bubbles into the electrolyte, which can be identified as "Releasing strategy" accordingly. In this contribution, an aerophilic electrode with cone shape is fabricated, from which the generated hydrogen bubbles can be timely removed through efficient and directional transportation (from tip to the base). Correspondingly, this approach is defined as "Transporting strategy". Furthermore, integrating the base of electrode with a superaerophilic sponge, which possesses excellent properties of efficiently absorbing and releasing gas bubbles, can realize the collection of generated hydrogen. It is believed that the present approach can contribute to promising applications in water electrolysis and will offer inspiration for fabricating novel hydrogen collector. Abstract : Hydrogen bubble adhesion on electrodes greatly impedes the widespread practical application of the hydrogen evolution reaction. In this work, a novel "transporting strategy" for efficiently removing the adhered hydrogen bubbles from the electrode is proposed. The transport is enabled by the conical morphology and aerophilic wettability of the electrode.